Pemberdayaan Pembudidaya Gurami Desa Tegalwangi Melalui Sosialisasi dan Pelatihan Pembuatan Abon - Rusmini; Sultan Adil Lanang Sejati; Wulandari, Yunita; Alexandria Nadya Ken Ababil (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2024)
The village of Tegalwangi, which is located in Umbulsari district, Jember District, is known as the "Gurami Village" because of its excellence in cultivation of gourami fish with an annual harvest of 3.8 quintals. Nevertheless, the gourmet farmers in this village face challenges in marketing as most fish are sold in raw form, which are susceptible to degradation and competing prices. The goal of the socialization and training program of the KKN Collaborative Group 110 is to empower local communities through the manufacture of abonnements of gourami fish, which are more durable and have greater added value. Surveys, information about the benefits of Gourami subscriptions, live subscription training, and product marketing are all parts of this activity. The results of this program show that Tegalwangi Village communities can build small and medium- sized enterprises (SMEs) based on gourami fish processing, strengthen the "Gurami Village" brand, and improve the village food resilience. The result is that the program has encouraged gourami farmers, explored local potential, and improved the village economy. To ensure business sustainability, community service must focus on product marketing aspects.